Hepatotoksikosis Awal Keracunan Kronis Aflatoksin B1 Pengarahnya Terhadap Spektruro Lipid Plasma Darah tikus - Wiryatun Lestariana Wiryatun Lestariana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
Plasma lipid spectrum studied included total lipid plasma, plasma triglyceride, plasma phospholipid and plasma cholesterol concentration in rats.1-listologically earlier hepatotoxicosis showed hyperplasia and metaplasia, and metaplasia of bile duct epithelial cells.The two groups of rats, the control group and the treatment group (each group comprised 10 rats). 3•month old, healthy, and 12 —16 g % haemoglobin concentration, were used as experimental animals. -All of them were fed and given water ad libitum, and 0.2 ml of propylen glycol per oral was also provided by sonde for 60 days. The treatment group was supplemented 10 mg of aflatoxin B, (AFB1) diluted in 0.2 ml propylen glycol.At the end of the treatment, histologically epithelial cells of bile duct showed extensive hyperplasia and metaplasia in rats supplemented with 10 rag AFB1. The plasma lipid spectrum between the control group and the treatment group was:plasma total lipid concentration (X ± 1 SD): 496.0 ± 12.61 mg/I00 ml and SO4M ± 10.46 mg/100 ml, plasma triglyceride concentration (X * 1 SD) 93.4 ± 14.83 mg/ l00 ml and 101.2 12.62 mg/100 ml. plasma phospholipid concentration (X ± 1 SD) 9.3 ± 4.21 mg/ l00 ml and 8.9 ± 3.92 mg/100 ml, plasma cholesterol concentration (X ± 1 SD) 106.9 t 17.56 mg/100 ml and 104.2 ± 12.53 mg/100 ml. The analysis test showed that there were no significant differences between blood plasma parameter of the two groups (p > 0.05).The result suggests that AFB, chronic toxicity on plasma lipid spectrum of rats is not proven despite the occurrence of earlier hepatotoxicosis. -Key Words: aflatoxin Bt -- hepatotoxicosis -- bile duct epithelial cells -- plasma lipid spectrum -- rat